DINAMIKA SILENT STRUGGLE PADA PESERTA DIDIK DAN RELEVANSINYA TERHADAP LAYANAN BIMBINGAN DAN KONSELING - Abidzar Al Ghifari; Septia Rosada; Fina Nikmatul Kamelia; Harits Mafaza Ahsan; Rahmi Anekasari (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
The phenomenon of silent struggle among students has become an increasingly relevant psychological issue in education, as many students experience emotional distress in silence without being able to express it openly. This study aims to examine the dynamics of silent struggle among students and its relevance to guidance and counseling services in schools. The research employed a qualitative approach using a library research method by reviewing various journals, books, and scientific literature related to students’ mental health, academic stress, and counseling services. The findings indicate that silent struggle is influenced by academic pressure, lack of emotional support, unsupportive social environments, introverted personality traits, and the influence of social media that triggers anxiety and insecurity. These conditions have an impact on decreased learning motivation, low academic participation, burnout, social anxiety, and academic procrastination. The study also emphasizes that guidance and counseling services play a strategic role in helping students cope with psychological pressure through individual counseling, group guidance, preventive approaches, and the creation of a humane, safe, and supportive school environment for students’ mental well-being.